An ontological Foucauldian reading of technologies of the self in selected novels of Samuel Beckett - Derabi, Javad Yaghoobi (2014)
As the overview of the past studies on Samuel Beckett shows, his fiction is not thoroughly analyzed in a framework which is both conceptual and standardized so that we can academically differentiate the modern or postmodern nature of his novels. The purpose of the present study is, thus, to offer a critical reading of the selected major fictional works of Samuel Beckett, The Trilogy. Its goals are to suggest a variety of interpretations that will encourage readers already familiar with Beckett’s novels to reevaluate his works and their implications and also to encourage new readers and students of literature to undertake further critical studies of his fiction. To that end the present study first explores Beckett’s selected novels - Molloy , Malone Dies and The Unnamable - in the light of the Foucauldian concept of the ‘Technologies of the Self’ to understand how does Beckett depict and portray the self as a key concept in the rudiments and characteristics of the postmodern novel; and second, the present thesis postulates to formulate a basic criterion by means of which we can yardstick the predominance of post/modern essence in Beckett’s novels as a possible academic strategy. The methodology here will be to evaluate Beckett’s trilogy in the light of critical concerns that have previously been, and are currently, discussed in the context of New Historicism, specifically speaking, the Foucauldian concept of the ‘Technologies of the Self’. In doing so, a further goal of this study is to reiterate and reinforce the value of what Brian McHale, in The Postmodern Fiction, refers to as a postmodern version of modernist literature and to contribute to the ongoing reevaluation of post/modern novel as critical idioms. This has been the main concern in chapter four of the present research to present a reading which encapsulates a discussion of the ‘Technologies of the Self’ across these novels. It also explicates on the existence of a more ontological nature,rather than that of an epistemological one to designate the postmodern stance rather than that of the modern one in these works therein addressing the inquiry: How is ‘self’ depicted and manifested in The Trilogy? With what the body of the voices of the self that The Trilogy reveals it appears to be titanically significant in answering the ontological question they are created to find an answer for. Molloy, Moran, Malone, The Unnamable and Mahood along with so many other surrogate characters for them want to leave stains and traces, to entertain, comfort, or guide their listeners as to whom they are. Thus, this research surmises that in The Trilogy,postmodernism precedes modernism through the ‘Technologies of the Self’ thereby creating a standard exemplary model for other possible case studies in ascertaining the blurring boundaries between the modern and postmodern novel. Each one of these novels provides the reader with an experiment that tests the limits of what it is to be a human, the ontological question of who am I here, the ontological question as the self keeps a voice resonating in a perusal so persistent that even the reader is not left untouched. They help the reader in having an experience of themselves and their world, and give them an increasing knowledge of the bodily and the linguistic limits of their modes of being, and create a stronger sense of their own flexibility.